The Applications of Clustering Methods in Predicting Protein Functions - Chen, Weiyang; Li, Weiwei; Huang, Guohua; Flavel, Matthew (Current Proteomics, 2019)
Background: The understanding of protein function is essential to the study of biological processes. However, the prediction of protein function has been a difficult task for bioinformatics to overcome. This has resulted in many scholars focusing on the development of computational methods to address this problem. Objective: In this review, we introduce the recently developed computational methods of protein function prediction and assess the validity of these methods. We then introduce the applications of clustering methods in predicting protein functions.
Keywords: Clustering